2015
DOI: 10.1063/1.4919968
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon enhanced fluorescence studies from aligned gold nanorod arrays modified with SiO2 spacer layers

Abstract: Here, we demonstrate that quasi self-standing Au nanorod arrays prepared with plasma polymerisation deposited SiO2 dielectric spacers support surface enhanced fluorescence (SEF) while maintaining high signal reproducibility. We show that it is possible to find a balance between enhanced radiative and non-radiative decay rates at which the fluorescent intensity is maximized. The SEF signal optimised with a 30 nm spacer layer thickness showed a 3.5-fold enhancement with a signal variance of <15% thereby k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…J-aggregate samples were prepared using meso-tetra (n-methyl-4-pyridyl) porphyrine tetra chloride (Frontier scientific) at pH=1 inducing J-aggregate formation by drop deposition as per reported procedures [19][20][21]. Reflection spectra from the nanorod array were measured in TE and TM polarizations and showed two broad bands associated with transverse and longitudinal modes from the nanorod array which are in line with literature reports (as shown in Figure 1(b)) [3,4,18]. Reflection spectra were recorded for the J-aggregate/nanorod sample as a function of (ΔR/R = (R sample − R background )/R background ) using a gold mirror background reference.…”
Section: Papersupporting
confidence: 70%
See 2 more Smart Citations
“…J-aggregate samples were prepared using meso-tetra (n-methyl-4-pyridyl) porphyrine tetra chloride (Frontier scientific) at pH=1 inducing J-aggregate formation by drop deposition as per reported procedures [19][20][21]. Reflection spectra from the nanorod array were measured in TE and TM polarizations and showed two broad bands associated with transverse and longitudinal modes from the nanorod array which are in line with literature reports (as shown in Figure 1(b)) [3,4,18]. Reflection spectra were recorded for the J-aggregate/nanorod sample as a function of (ΔR/R = (R sample − R background )/R background ) using a gold mirror background reference.…”
Section: Papersupporting
confidence: 70%
“…SEM studies (using a Jeol 6500F field emission SEM) reported that the Au nanorod substrate possesses a 70 ± 11 nm array period (center to center distance), a rod diameter 35 nm ± 7 and rod height of 200 ± 25 nm. The nanorods are encased in an anodic aluminum oxide (AAO) template which was removed prior to sample preparation via an etching solution in 30 mM NaOH as reported previously [3,4,18]. J-aggregate samples were prepared using meso-tetra (n-methyl-4-pyridyl) porphyrine tetra chloride (Frontier scientific) at pH=1 inducing J-aggregate formation by drop deposition as per reported procedures [19][20][21].…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…One route to enhance the Raman signal is to use plasmon‐active nanomaterials in order to detect a highly specific chemical fingerprint for a wide range of analyte molecules . Such an approach is often referred to as surface‐enhanced Raman scattering (SERS), with typical enhancement factors of ~10 8 –10 10 . The ability of SERS to detect analytes (down to the single‐molecule level SERS) benefits significantly from the formation of regions with high electromagnetic field intensities (“hot spots”) such as a nanoscale (<10 nm) junction between two metal NPs .…”
Section: Introductionmentioning
confidence: 99%
“…12,16,19,21,26,30 Therefore, it is essential to control the distance between the fluorophores and the particles surface. 12,14,16,19,21,26,31 In order to achieve such distance control, the use of different types of spacers has been reported such as silica, 22,24,[32][33][34][35] polymers, 7,19,21,[36][37][38][39] and biomolecules. 28,[40][41][42] However, one important factor is yet unconsidered.…”
Section: Introductionmentioning
confidence: 99%